2018
DOI: 10.5539/ijbm.v13n7p137
|View full text |Cite
|
Sign up to set email alerts
|

Wine Marketing: Consumer Persuasion through the Region of Origin

Abstract: This study aims to examine the effectiveness of the communication of the region of origin – through either pictorial or pictorial-textual formats – in print advertising messages for wine bearing a GI label. An experimental design was used to manipulate the region of origin presentation in print advertisement (absent vs pictorial vs pictorial-textual) while measuring participants’ attitude towards advertisement and purchase intention (dependent variables). Results provide empirical support to the appropriatenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In contrast to the regression models for Northern Italy, goodness of fit of the regression models for Southern Italy remains relatively low. Finally, the influence of sympathy for a region on the probability of buying a wine falls in line with other findings, which, especially for this product, ascertain an influence of positive attitudes (affective component) as well as cognitive aspects on consumer perception (van Ittersum 2002;Latusi et al 2018). Even though the normative image differs significantly between Northern and Southern Italy, it has no discernible influence on purchase probability.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In contrast to the regression models for Northern Italy, goodness of fit of the regression models for Southern Italy remains relatively low. Finally, the influence of sympathy for a region on the probability of buying a wine falls in line with other findings, which, especially for this product, ascertain an influence of positive attitudes (affective component) as well as cognitive aspects on consumer perception (van Ittersum 2002;Latusi et al 2018). Even though the normative image differs significantly between Northern and Southern Italy, it has no discernible influence on purchase probability.…”
Section: Discussionsupporting
confidence: 86%
“…Their findings show that effects of origin tend to be region-specific and certain products are subject to a stronger regional effect than others. Thus Latusi et al (2018) argue analogously, that the link between a geographical (regional) indication and the product wine helps to reduce consumer's risk perception by also reducing concern about the origin and production method of the product. Regional indications of origin can thus serve as an extrinsic cue for perception differentiation and risk reduction on a regional basis, which ultimately leads to an increase in purchase probability (Latusi et al 2018).…”
Section: The Role Of Attitude In Purchasing Behaviour Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have primarily focused on investigating country-of-origin image as a homogeneous national construct, recent research has shown that regional differences and tendencies exist in a country’s image, which can significantly influence how people perceive products from that country [ 8 , 9 ]. According to Šapić et al [ 10 ], the concept of "country of origin image" is one of the most studied concepts by social scientists, which emerged from manufacturers’ decision to internationalize their business operations and offer their products in foreign markets.…”
Section: Introductionmentioning
confidence: 99%